2005
DOI: 10.1177/174701610500100304
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Ethical Review of Qualitative Research

Abstract: In recognition of the important ethical issues posed by qualitative research in health care, the authors present key questions to aid ethical review. The purpose is to assist lay and professional members of research ethics committees in their assessment of applications involving qualitative research methods and to inform researchers intending to submit such applications for ethical approval. For the benefit of those less familiar with this type of research, the authors include an overview of different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
6
0
3
Order By: Relevance
“…Additionally, lay participants might have unconsciously or consciously mimicked the intentions of researchers due to self-selection bias and reporting bias because they agreed to participate in the study. To evaluate data credibility, JH, ND and another researcher (AO) who did not participate in running the program conducted a triangulation of the data (Walker, Holloway, & Wheeler, 2005). We assessed data that arose from free, frank and honest interactions and found that the group which included one particular researcher (JH) maintained a good relationship in which everyone asked frank questions or provided dissenting opinions.…”
Section: A Strengths and Limitationsmentioning
confidence: 99%
“…Additionally, lay participants might have unconsciously or consciously mimicked the intentions of researchers due to self-selection bias and reporting bias because they agreed to participate in the study. To evaluate data credibility, JH, ND and another researcher (AO) who did not participate in running the program conducted a triangulation of the data (Walker, Holloway, & Wheeler, 2005). We assessed data that arose from free, frank and honest interactions and found that the group which included one particular researcher (JH) maintained a good relationship in which everyone asked frank questions or provided dissenting opinions.…”
Section: A Strengths and Limitationsmentioning
confidence: 99%
“…How, then, can ethical review committees make the required judgement about appropriate qualitative experience, qualifications and competence? Although previous articles (including in this journal) have examined the ethical issues arising in qualitative research practice (Miller et al, 2012; Richards and Schwartz, 2002; Shaw, 2008; Walker et al, 2005), none addresses the specific issue of research competence. Thus, the aim of this article is to provide guidance to members of ethical review committees who have a responsibility to assess qualitative research competence.…”
Section: Research Competence Is An Ethical Requirementmentioning
confidence: 99%
“…Some indicators of research in/competence related to ethical practice are as follows: Does the researcher seem to have an awareness of, and address, specific ethical issues related to their chosen methodological design? Literature on ethical practice in qualitative research provides a useful resource here (Miller et al, 2012; Richards and Schwartz, 2002; Shaw, 2008; Walker et al, 2005), as does the National Statement’s Chapter 3.1 Qualitative Methods (National Health and Medical Research Council, 2007 (revised 2015)). Areas we would expect to be addressed include: relationships between researcher and participants, especially in designs involving participant observation and repeated engagements (e.g.…”
Section: Ascertaining Research Competencementioning
confidence: 99%
See 2 more Smart Citations